Defect model of domain nucleation growth induced by interlayers in poly (vinylidene fluoride-trifluoroethylene) ultrathin films. (22nd January 2021) - Huang, Zhiqiang; Zhang, Xiuli; Li, Xingjia; Zhu, Guodong; Meng, Xiangjian; Shi, Zhi; Zhang, Dandan; Sun, Xiaohui
Abstract: The polarization switching behaviors of ultrathin films of ferroelectric poly(vinylidene fluoride-trifluoroethylene) capacitors with different electroactive interlayers have been studied. The polarization switching results are related to the high local electric field and complete microdynamic switching behavior can be ensured by optimizing the defect model. Weiss mean field theory was introduced to analyze the nucleation process of defect states. The spatial defects around the ferroelectric domain were aligned, resulting in a stable space configuration with low energy. Three hypothetical effects are proposed based on the recovery mechanism of dipole defects, including the obedience effect, cooperation effect and antagonism effect. Understanding and controlling defect functionality in ferroelectric materials is critical for realizing reliable applications in ferroelectric memories.